Land Use Change: Science, Policy and Management - Aspinall, Richard (CRC Press, 2009)
Changes in the use of land reflect a variety of environmental and social factors, necessitating an equally varied suite of data to be used for effective analysis. While remote sensing, both from satellites and air photos, provides a central resource for study, socio-economic surveys, censuses, and map sources also supply a wealth of valid information. Land Use Change: Science, Policy, and Management presents spatial theories and methodologies that support an integrated approach to the analysis of land use change. Focusing on spatial representation and modeling, this book addresses such important scientific issues as the dynamics of change, integration and feedback between system elements, and scale issues in space and time.